STRETCHING: ONE HEALTHY PRACTICE - STUDY OF ITS INFLUENCE ON THE FLEXIBILITY (Fiep Bulletin - online, 2014)
This study brings for the debate the relations among physical aptitude, quality of life and public health, when dimensioning the epidemiologist aspects of flexibility. In this direction we focused our study subject concerning the regular physical exercise under the physical perspective. First we have done a literature review on the possible benefits stretching, as a modifier instrument  of the flexibility physical capacity in its aspects. The main aim of this research was to analyze the effectiveness of a stretching physical exercise program, on the joint mobility, through the use of Active the Static method and Static Liabilities. The sample was composed of 16 women, between 22 and 30 years of age who join the " Alongamento:uma prática saudável" couse, three times a week, 60-minute-session. The tests had included   shoulders,  trunk,  hip and knees flex moviments. The data collected had two phases the initial and final with an interval of ten weeks, and we have worked with descriptive statistics and the resultes have shown a quantitative improvement in flexibility. We can consider that this corporal practice has presented positive results when applied in a ten weeks period, resulting in an joint amplitude increase.
Keywords: Stretching; Flexibility; Life Quality